MINAT BELAJAR MATEMATIKA SISWA DI MASA PANDEMI COVID-19 DITINJAU DARI PERSPEKTIF GENDER - Herti Prastitasari; Noor Mairin Isnani; Jumadi; Dessy Dwitalia Sari; Wardhani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes an overview of elementary school students' interest in learning mathematics during the COVID-19 pandemic era based on a gender perspective through the indicators of students’ interest in learning. They are the feelings of pleasure or like towardsmathematics, students’ interest in learning mathematics, students' attention to learning mathematics, students’ involvement in the process of learning mathematics, and the satisfaction learning mathematics. The method used was qualitative with case study research. Researchers, teachers, and students consisting of 3 male and 3 female students came from one public elementary school in Tapin. Data collection techniques used observation, questionnaires, documentation, and interviews. Based on the results of data analysis, it was found that there were differences based on students’ interest in learning between male students who obtained a percentage score of 97.50% and female students who obtained a score of 96.67%. The data showed that male students were more interested in learning than female students. Yet, the difference was not significant. This finding indicated that in the process of learning mathematics, gender differences were not a variable that determined differences of students' interest in learning. Hence, in learning mathematics at elementary schools, the important thing was how teachers presented teaching and learning interestingly in order to make students have a good interest in learning.